Prediction of initiation and ends dates of moderat and sever frosts in Kermanshah province selected on the outputs of some climate models - Broomand Salahie; Mahdei Aeli Jaham; Saiede Ainei; Jafar Derakshei (نشریه جغرافیا و برنامه‌ریزی, 2017)
The purpose of this study is forecasting the moderat and severs frost of three stations in Kermanshah, Kangavar and Sarpolezahab using output of the LARS-WG downscale model in the next two decades. The Input data's of models used in this study are: precipitation, minimum temperature, maximum temperature and radiation in daily scale during the period 1992 - 2012. In the present study, using the output of two climate models, HADCM3 and BCM2 Under A1B Scenario, the initiation and end of the moderat and sever frost in these three periods 2030-2011, 2065-2046 and 2099-2080 have been evaluated. The results of the LARS-WG model process by the means of two Scheme Bcm2 and Hadcm3 indicate the warming of these stations in the coming years. The initiation of the moderat frost in these pointed stations is going to April by passing time. Between the stations in which are under study, Kangavar and Kermanshah stations have similar behavior but the Sarpolezahab station because of its tropic characteristic, showed  a different behavior rather than the two stations in the coming years. The beginning of sever frost of these stations delayed with passing time and proceeds toward spring and in the other side, the end time of the last sever frost by passing time and getting close to the end of the anticipated period, is toward the beginning of winter and even at the Sarpole-zahab station until February. According to the results of the processing these models, the number of days with the moderat and sever frost in these stations will be dwindled in the coming years and the trend of temperature in these stations will be increased.